Autoimmune encephalitis associated with antibodies against intracellular antigens in children - Zhang, Linlin; Che, Chao; Han, Xingyu; Cao, Aihua (Frontiers in Immunology, 2026)
BackgroundIn neurological disorders associated with autoantibodies against intracellular antigens, response to therapy tends to be poor and is associated with irreversible neuronal death. This study aimed to analyze autoimmune encephalitis (AE) associated with antibodies (Abs) against intracellular antigens in children, clarify the clinical characteristics of the disease.MethodsWe retrospectively analyzed patients with Abs against intracellular antigens at Qilu Hospital of Shandong University from 2024 to 2025. Detailed clinical characteristics were collected based on AE-Abs test results.ResultsFourteen pediatric patients with AE caused by intracellular Abs were recruited. The Abs included PCA-2, AGO, GFAP, SOX1, Ri, Yo, KLHL11, and AK5. All the patients received immunotherapy. After treatment, the antibody titers in the cerebrospinal fluid and serum of patients mostly decreased or even turned negative. Some patients were discharged with sequelae.ConclusionIn AE associated with Abs against intracellular antigens of children, seizures were the most common clinical manifestation. For patients with seizures without obvious inducement or suspected encephalitis, AE-related Abs should be detected promptly, and immunosuppressive therapy should be administered as early as possible. The prognosis of pediatric patients with encephalitis with Abs differs from that in adults, and most patients recover well after active treatment.